Food Security Condition of Landless People in a Char Area of Rangpur District (Progressive Agriculture, 2014)
The study was conducted to investigate the food security condition of households of landless char people at Purba Isli village of Lakshmitary union, Gangachara Upazila of Rangpur District. Data were collected from a random sample of 80 where the total landless char people were 400. A structured interview schedule was used for collecting data during April to May 2012. Food security condition of households of landless char people was measured on the basis of their per capita calorie consumption per day. Coefficient of correlation (r) was computed to explore relationship of the respondents selected characteristics and their food security condition. More than half (57.5 per cent) of the households were food secure and energy intake was 2122 kcal/person/day. On the other hand, 21.3 per cent household were food insecure and consumed between 1805 and 2121 kcal/person/ day and 21.3 per cent households were found severely food insecure and calorie intake was less than 1805 kcal/person/day. Thus, it can be concluded that nearly half of the landless char people were food insecure. Landless char peoples year of schooling, landlessness category, annual household income, training experience, and credit received, extension media contact, involvement in NGO, perceived strategies to cope with food insecurity and perception of organizational food insecurity mitigation initiatives had significant positive relationship with their household food security condition.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19180 Progress. Agric. 24(1&2): 281 - 289, 2013